Efektivitas Micronecta sp sebagai Pengendali Biologis Vektor Demam Berdarah Dengue - Malik Saepudin; Bambang Supraptono; Iswono Iswono; Marvita Marvita (Buletin Keslingmas, 2026)
Dengue hemorrhagic fever remains a persistent public health problem, while insecticide-based control is constrained by transient impact and the emergence of resistance. This study assessed the effectiveness of Micronecta sp. integrated into Water Reservoir Plus (WRP) as a biological predator of Aedes aegypti larvae and explored its potential implications for dengue transmission through transovarial mechanisms. A true experimental posttest-only control group design was conducted in RW 18 Siantan Hulu, Pontianak (2025). Five groups comprised a control and WRP treatments containing 5, 10, 15, or 20 Micronecta sp.; each group had six replicates with 50 first–second instar larvae per replicate (1,500 larvae in total). Data were analyzed using normality and homogeneity tests followed by one-way ANOVA and Tukey post hoc (α=0.05). Mean larval predation increased with predator density (3.33 and 3.17 larvae at 5 and 10 predators; 6.33 at 15 predators; 8.33 at 20 predators), whereas the control group averaged 1.33 larvae. Between-group differences were significant (p<0.05), and the 20-predator configuration yielded the highest predation. The observed dose–response pattern indicates that predation capacity was not saturated within the tested range, supporting WRP-based Micronecta sp. as a feasible, environmentally friendly larval control approach. Virological testing is required to verify any impact on vertical dengue transmission.